Comparing the situation and person-based predictors of work–family conflict among married working professionals in India. Issue 5 (24th September 2019) - Baral, Rupashree
Abstract : Purpose: The purpose of this paper is to ascertain the situation (presence of young children, working hours, social and organizational support) and person-based factors (core self-evaluations) that influence work-family conflict (both work-to-family conflict (WFC) and family-to-work conflict (FWC)) and to examine the relative power of situational factors vs person-based factors in predicting work-family conflict. Design/methodology/approach: Data were collected from 367 married working professionals from eight organizations in the manufacturing and services sector in India. Hierarchical regression analysis was conducted to test the hypotheses. Usefulness analysis was performed to reveal the unique contribution of the dispositional variables over the situational variables in predicting the variance in work-family conflict. Findings: Personality factors accounted for more variance in FWC than in WFC, and situational factors accounted for more variance in WFC than in FWC. Research limitations/implications: Given the limitations associated with a cross-sectional design, caution is needed concerning the inferences drawn. Only a few variables are considered to assess the characteristics of the context. Practical implications: Organizations should not view the resolution of work-family conflict as the sole responsibility of an individual because of the demonstrated influence of both dispositional and contextual factors on the presence or absence of such conflict. While individuals may strive to have better self-management skills and stay positive in adverse situations, employers may assist them in dealing with work-family demands by introducing need-based support. Originality/value: The relative importance of situation-based and person-based variables in predicting work-family conflict has rarely been examined on a managerial sample in India. Research on personality-based antecedents of work-home interference is also in its infancy. A better understanding of the factors as they relate to both directions of work-family conflict may help to identify suitable approaches to managing conflict.